Aplikasi Pewarnaan Artistik Metode Ganda dengan Teknik Frosting untuk Mendapatkan Warna Pirang Tembaga - Megasari, Dindy Sinta; Singke, Juhrah (Journal of Beauty and Cosmetology (JBC), 2020)
Hair dyeing has developed fast in which a dual application method with frosting technique is much favored by many teenagers. This study aimed to find out the result of hair dyeing using the dual application method with frosting technique on oily and dry hair types and reveal the comparison of the hair dyeing results that best matches the copper blonde color index between oily and dry hair types. This study used experimental research design with two groups. Group A was the oily hair type treated using oxidation cosmetics dye with copper blonde color while Group B got the same treatment but applied to the dry hair type. Data were collected using observation administered by 24 experts. The results of the study portrayed that the dual application method with frosting technique was way better applied for oily hair type than the dry hair one.